Clinical Profile and Outcome of Multisystem Inflammatory Syndrome in Children (MIS-C): A Retrospective Study - Milind M Suryawanshi; Chandrakant M Bokade; Dipak M Madavi; SHAMAMA SUBUHI; LAKSHMIKANT A ROHADKAR; Anwesha Singh (JCDR Research and Publications Pvt. Ltd., 2022)
Introduction: Multisystem Inflammatory Syndrome in Children (MIS-C) is a life-threatening complication of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection. It can also present with multisystem involvement including circulatory shock, systemic inflammation, and mucocutaneous and dermatologic involvement. Children infected with Coronavirus Disease-2019 (COVID-19) are mostly asymptomatic but those having co-morbidities are at a greater risk of getting severe infections. Aim: To study the clinical profile and outcome of children with MIS-C. Materials and Methods: This was a single-centre retrospective hospital-based observational study conducted at Indira Gandhi Goverment Medical College, Nagpur, Maharashtra, India. MIS-C protocol was developed at the Institutional level as per the World Health Organisation (WHO) and Indian Academy of Paediatrics (IAP) guidelines. Children admitted with MIS-C upto the age 18 years, were included as per the diagnostic criteria of MIS-C given by the WHO. The data pertaining to the demographics, clinical findings, underlying comorbidities, echocardiographic findings, laboratory investigations, and treatment received including intensive care interventions and outcomes were obtained from patient hospital records from 1st May 2021 to 30th September 2021.These collected data were obtained and statistical analysis was performed in patients treated for MIS-C. Results: The study included 18 children, who were diagnosed with MIS-C, with a median age of six years. Most of them presented with fever 12 (66.67%), followed by gastrointestinal symptoms 11 (61.1%). Elevated levels of C-reactive protein were found in all of them (58.04±34.87mg/L). The majority of children needed intensive care admissions 17 (94.45) and vasoactive medications were given to 8 (44.45%) children. Steroids were given in all children and Intravenous Immunoglobin (IVIG) in 7 (38.9%), and a combination was used in 10 (55.55%) children. Co-morbidities were seen in 4 (22.22%) children (two sickle cell disease, one diabetes mellitus type 1, and one had global developmental delay. Mortality was noted in 4 (22.22%) children, and none of them had any co-morbidities. Conclusion: The majority of the children with MIS-C in this study presented with acute febrile illness and shock and required intensive care. In children with pre-existing comorbidities, the outcome is surprisingly good